2022
DOI: 10.1021/jacs.2c08491
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium Pincer Complexes and Their Applications in Catalytic Semihydrogenation of Alkynes and Hydrogenation of Alkenes: Evidence for Metal–Ligand Cooperation

Abstract: The development of catalysts for environmentally benign organic transformations is a very active area of research. Most of the catalysts reported so far are based on transition-metal complexes. In recent years, examples of catalysis by main-group metal compounds have been reported. Herein, we report a series of magnesium pincer complexes, which were characterized by NMR and X-ray single-crystal diffraction. Reversible activation of H2 via aromatization/dearomatization metal–ligand cooperation was studied. Util… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
38
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 79 publications
2
38
0
1
Order By: Relevance
“…As a very recent example, Milstein and co-workers have evidenced the great potential of Mg pincer complexes as catalysts for the transformation of diphenylacetylene derivatives to the corresponding (Z)-alkenes with good to very good diastereoselectivities. 11 Previously, our groups have also shown that low-valent Mo pincer complexes and cuboidal Mo 3 S 4 clusters are also efficient homogeneous catalysts for this transformation. 12,13 Notably, pincer complexes utilizing sophisticated phosphine ligands dominate this chemistry and more importantly, mechanistic investigations on these systems have revealed unique reaction pathways.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…As a very recent example, Milstein and co-workers have evidenced the great potential of Mg pincer complexes as catalysts for the transformation of diphenylacetylene derivatives to the corresponding (Z)-alkenes with good to very good diastereoselectivities. 11 Previously, our groups have also shown that low-valent Mo pincer complexes and cuboidal Mo 3 S 4 clusters are also efficient homogeneous catalysts for this transformation. 12,13 Notably, pincer complexes utilizing sophisticated phosphine ligands dominate this chemistry and more importantly, mechanistic investigations on these systems have revealed unique reaction pathways.…”
Section: Introductionmentioning
confidence: 92%
“…7,9 In the case of Mg, a metal-ligand cooperation mechanism (MLC) involving the aromatization/dearomatization of the pincer compound is proposed. 11 Interestingly, trinuclear Mo 3 S 4 clusters containing inexpensive diamino ligands also catalyze the semihydrogenation of diphenylacetylene (dpa) with an acceptable (Z)-stereoselectivity (Z/E ca. 6/1) in the absence of a base, albeit harsh conditions were required (12% mol catalyst, 100 bars of H 2 and 150 °C) to achieve moderate conversion (ca.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to stoichiometric reactions, the geometrically constrained aluminum and phosphorus compounds serve as efficient catalysts for the dehydrogenation of amines and formic acid and for the hydroboration of imines and ketones, respectively . Recently, magnesium and zinc pincer complexes have been shown to act as efficient catalysts for catalytic hydrogenation reaction, which proceeds by aromatization and dearomatization element–ligand cooperation . The reactivity of these compounds originates from the cooperation of the electrophilic main-group element centers with the nucleophilic ligands.…”
Section: Introductionmentioning
confidence: 99%
“…Frustrated Lewis pair (FLP) systems, featuring boranes in combination with a Lewis basic moiety, are some of the most successful homogeneous nontransition metals capable of the selective semi-hydrogenation of internal alkynes. During the revision of this work, Milstein and co-workers reported a Mg-based catalyst for alkyne semi-hydrogenation . Herein, we report the activation of H 2 by the 1,2-addition across a Zn–N bond of a novel zinc anilide complex.…”
Section: Introductionmentioning
confidence: 99%